Information levels in additive group decision models under incomplete information: Bridging the cardinal ordinal gap - Vetschera, Rudolf (2015)
In the literature, several models for group decision making based on the additive aggregation of group members’ utility or value functions have been proposed (Keeney and Kirkwood 1975; Dyer and Sarin 1979; Keeney and Nau 2011). These group aggregation rules usually are based on systems of axioms very similar to those formulated by Arrow (1963) for the case of aggregating ordinal preferences. In contrast to aggregation of ordinal preferences, aggregation of cardinal alues is thus possible in groups. However, it requires group members to specify their preferences in cardinal form, by assigning utility scores to alternatives. This could be difficult for group members, in particular if this information should be provided exactly.